Truth, objectivity and evolution. Darwinian evolutionary theory from the approach of Karl Popper’s epistemology - Jaimes Álvarez, Freddy Roberpierre (2021)
This essay presents the ideas of Karl Popper around the problem of truth, objectivity, falsification and deductive logic and how these are related to the theory of Darwinian evolution. The idea of the evolutionary character of Popperian ideas about knowledge, in general, and scientific knowledge in particular, will be defended, with special attention to how Darwin's theory of evolution plays a very important role in the development of an Popperian evolutionary epistemology. It begins with an exposition on Popper's contribution to epistemology and, later, on the role of the Darwinian theory of evolution in the development of a vision of science as a generator of theories and progress through the deductive method.